(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: To describe the characteristics of dyslipidemia in type 2 diabetes patients at An Phuc General Clinic. Subjects and methods: Prospective cohort study, describing 172 patients diagnosed and treated for type 2 diabetes with primary dyslipidemia at An Phuc General Clinic, from February 2021 to October 2021. Results: The percentage of patients with increased serum TG accounted for the highest rate with 72.09%, followed by patients with elevated serum cholesterol accounting for 55.81%. The rate of patients with multiple index disorders was 30.81%. The rate of increased LDL-C level was quite high with 38.95%. Conclusion: Mainly diabetic patients had dyslipidemia with increased serum TG followed by increased serum cholesterol.